THE EFFECTIVENESS OF THE IMPLEMENTATION OF ONLINE ENGLISH LEARNING DURING THE COVID-19 PANDEMIC ERA OF THE EIGHTH GRADE STUDENTS AT STATE JUNIOR HIGH SCHOOL 2 OF RAMBANG NIRU MUARA ENIM - Anzal Fajariah (Esteem Journal of English Education Study Programme, 2021)
This study aims to determine the effectiveness of online learning in learning English in the eighth grade students at state Junior High School 2 of Rambang Niru, Muara Enim. The questions are the questions that this research may try to answer: 1)How is the implementation of online  English learning during the Covid-19 pandemic era at   the  eighth grade?2)How is the effectiveness of online  English learning perceived by students, teachers and parents in English learning during the Covid-19 pandemic era 3) What are the drawbacks of the effectiveness of online learning   perceieved  by at the eighth grade ?This research using the Qualitatif method. The findings of this study found the ineffectiveness of online English learning.